HIJRAHTAINMENT: COMPOSING PIETY AND PROFANE AS COMMODIFICATION OF RELIGION BY MEDIA - Ratri Rizki Kusumalestari (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2020)
According to the constructionism paradigm in communication and media theory, social reality is constructed by the media based on its ideology. The media construct various realities in the real world into a second reality. One of them is the rise of artists who explore Islam and decide to